STUDENTS"™ PERCEPTION ON DRAMA SUBJECT IN SUPPORTING THEIR SPEAKING PERFORMANCE - Sanditia, Elma; Rosnija, Eni; Susilawati, Endang (International Journal of Learning and Instruction (IJLI), 2025)
Abstract  This research is aimed to find out the students"™ perception of drama subject in supporting their speaking performances in the English Education Study Program at Universitas Tanjungpura. In this research, the researcher used qualitative descriptive method. The data were collected utilizing a questionnaire with 15 characteristics paired with a 5-point Likert Scale instrument ranging from "strongly disagree" to "strongly agree" to assess students' speaking perception. In this study, the researcher discovered that the total students' perception of sixth-semester students at Universitas Tanjungpura was 4.10, which was classified as a favorable perception.Based on the data it can be concluded most of the sixth-semester students felt that drama has a positive effect on their language aspects physiological aspects, performance condition, and strategy of teaching and learning.  Keywords : Students"™ Perception, Drama, Speaking Performance